The Relationship between Learning Motivation with Discipline Learning Students in Al-Qur'an Education Masjid Baitussalam Padang City - Elsa Rizanita; Tasril Bartin (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
This research is motivated by the low learning discipline of students in the Taman Pendidikan Al-Qur’an Masjid Baitussalam Kota Padang which allegedly has to do with students' learning motivation. The purpose of this study was to look at the picture and the relationship between students' learning motivation in the Taman Pendidikan Al-Qur’an Masjid Baitussalam Kota Padang. This research is wholly rational, which is looking at the relationship between learning motivation and learning discipline. The research population is the students of the Taman Pendidikan Al-Qur’an Masjid Baitussalam Kota Padang, with a total population of 64 people. The research sample of 32 people taken 50% of the population. The research instrument used to collect data on learning motivation and learning discipline is a questionnaire, using a Likert scale with 4 alternative answers namely: always, often, rarely, and never. Meanwhile, to measure the results of the research data, it is carried out using descriptive formulas and product moments. The results showed that students have a discipline of learning and low motivation to learn, and there is a significant relationship between learning motivation and learning discipline of students in the Taman Pendidikan Al-Qur’an Masjid Baitussalam Kota Padang, this is evidenced by the results of the calculation of correlation using the product-moment formula which shows that the r count (0.495) is greater than rtable both at the 99% confidence level (0.463) and 95% confidence (0.361).Keywords: Students, Learning Motivation, Learning Discipline